Determination of engineering geophysical parameters of grounds on building sites and for seismic microzonation (methodical and metrological components of technology) - Bondarenko, M.S.; Kulyk, V.V. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2022)
To ensure the reliability and long-term usage of high housing buildings, important industrial, infrastructural and other objects, it is necessary to carry out engineering geological investigations of grounds (near-surface rocks) as the basis of these structures. To prevent the potential danger of destruction of the objects, it is also necessary to perform microseismic investigations of the near-surface geological environment and to agree the obtained results with the engineering geological parameters in the section of the test boreholes. Engineering geological parameters, determined by geophysical methods, are named engineering geophysical parameters. To solve the geophysical engineering problems, including seismic microzonation, at the Institute of Geophysics of the National Academy of Sciences of Ukraine a modern investigation technology has been created. The technology is based on apparatus and methodical complex of radioactive logging, which involves gamma-ray logging (GL), density logging (DL) and neutron logging (NL). This paper presents the results of developing adequate methodical and metrological assurance of the radioactive logging complex as a key technology element. Complexation of methods GL, DL and NL (taking into account a priori data) and the use of the proposed approaches allow determining a wide set of engineering geophysical parameters: density, porosity, volume moisture, groundwater level, the content of shale, the content of clay minerals, water saturation, dry ground density, etc. The features of obtaining parameters by the radioactive logging complex in the zone of aeration and the zone of saturation are shown, as well as taking into account the influence of the shaliness on the determined parameters. The effectiveness of the technology has been demonstrated by specific examples and confirmed by independent laboratory measurements.